The The Role of Online Disinhibition Towards Cyberbullying on Second-Account Users on Instagram - Emi Zakiah; Rosada Dwi Iswari (Universitas Nusa Cendana, 2022)
This study aims to determine the role of online disinhibition towards cyberbullying on second-account users on Instagram. The participants of this study were 150 second-account users on Instagram. The sampling technique used was purposive sampling. Online disinhibition is measured using a scale compiled by researchers based on the aspects proposed by Stuart & Scott (2020). Cyberbullying is measured using the cyberbullying scale, which is also compiled by researchers based on aspects proposed by Langos (2012). Data analysis was performed using simple regression techniques. Data analysis resulted in the value of R square = 0.520 F = 160.136 and p = 0.000 (p <0.005). Data analysis resulted in a value of p = 0.000 (p <0.005), which indicated that there was a role for online disinhibition in cyberbullying with an R square = 0.520, which means that it gave a role of 52%.